Identification and Categorization of Misconceptions on Mutations in Highschool Biology Textbooks - Mohammad Alfin Rizkiandi; Wolly Candramila; Andi Besse Tenriawaru (Tropical Genetics, 2026)
This study examined misconceptions found in Grade XII Biology textbooks, specifically in the topic of mutation. A qualitative descriptive approach was employed using content analysis on four Biology textbooks commonly used in senior high schools in Pontianak. Key concepts were identified based on Core Competency 3.8 and compared with credible references from genetic literature. Potential misconceptions were verified by two experts and categorized into five types of errors according to the classification by Dimenli, Cardak, and Oztas: misidentification, oversimplification, overgeneralization, undergeneralization, and outdated concepts or terminology. Data validity was ensured through triangulation techniques involving teacher interviews, textbook content analysis, and documentation. The results indicate that two out of the four textbooks analyzed contain several misconceptions in presenting mutation material, ranging from definitions and types of gene mutations to chromosomal mutations. These findings highlight the importance of evaluating textbook content as a primary learning resource to prevent conceptual misunderstandings among students. This research is expected to serve as a reference for teachers and students in selecting and utilizing Biology textbooks more critically.